2009
DOI: 10.5539/ijbm.v4n1p26
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge Review: Implications For Future Research and Practical Application

Abstract: Knowledge has evolved from being an abstract concept that resides within the human mind to a manageable resource that is capable of contributing to organisational competitive advantage. Research in the field is largely divergent, both in methodological execution and in objective, resulting in potential for a widening of the gulf between scholastic endeavour and practical value. A 'Knowledge Matrix' based upon Tranfield and Starkey's (1998) social and cognitive dimensional conceptualisation is used to depict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…KM processes entail generating, codifying, storing, sharing and using knowledge (Aurum et al , 2008; Mikic et al , 2009). This implies that public sector organisations, need a system that will contribute towards knowledge production, acquisition, classification, storage, dissemination and use/re-use of knowledge (Guide of Knowledge Management in the Federal Government, 2017; A toolkit for South African municipalities, 2013; Becerra-Fernandez and Sabherwal, 2010; Alavi and Leidner, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…KM processes entail generating, codifying, storing, sharing and using knowledge (Aurum et al , 2008; Mikic et al , 2009). This implies that public sector organisations, need a system that will contribute towards knowledge production, acquisition, classification, storage, dissemination and use/re-use of knowledge (Guide of Knowledge Management in the Federal Government, 2017; A toolkit for South African municipalities, 2013; Becerra-Fernandez and Sabherwal, 2010; Alavi and Leidner, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This model of tacit and explicit knowledge conversion was built on Polanyi's () work ‘personal knowledge’, which suggested that knowledge resides in the minds of the individual, being organisational and practical and is considered to be the central model of organisational knowledge creation. It also brings together a wide range of KM processes such as generating, codifying, transferring and utilising knowledge (Haggie and Kingston, ; Rice and Rice, ; Aurum et al ., ; Grant and Grant, ; Mikic et al ., ).…”
Section: Introductionmentioning
confidence: 99%